Enhancement of packaging quality and digital marketing management for SuleMu soy milk - Triastuti Rahayu; Guntur Nurcahyanto; Ima Aryani; Muhammad Halim Maimun; Arum Dyah Ripdianti (Community Empowerment, 2024)
SuleMu is a soy milk product produced by KL LazisMu SMP Muhammadiyah 7 (SMP MUTU) Colomadu, Karanganyar Regency, Central Java Province. Although SuleMu packaging has a label, it lacks nutritional information. Additionally, its marketing strategy is still traditional. Therefore, this community service aims to add nutritional information to SuleMu packaging and create a digital marketing platform. The implementation of this program began with coordination, nutritional analysis, packaging label redesign, digital marketing training, the creation of a SuleMu digital marketing platform, and evaluation. The results of the nutritional analysis of SuleMU per 100g were: protein (3.4g), fat (3.3g), sugar (5.1g), crude fiber (2.6g), and calcium (40mg). This data has been added to the new SuleMu label. For digital marketing training, the average pre-test scores for WhatsApp Business and Instagram materials were 72.57 and 73.14, respectively, while the average post-test scores were 87.43 and 81.43. SuleMu also now has digital marketing accounts on Instagram and WhatsApp Business.